Process Intensification in Gas-Liquid Mass Transfer by the Introduction of Additives: A Review - Huan Zhang, Bo Zheng, Ping Chang, Tao Yu and Chengtun Qu (Nature Environment and Pollution Technology, 2023)
To overcome the challenges of the increasing global energy and to solve the global energy & environment problems, process intensification is one way to develop new efficient production pathways for the chemical industry. Process intensification plays an important role in the gas-liquid mass transfer processes. This review provides an overview of the developments in gas-liquid mass transfer enhancement. A major enhancement method, namely introducing additives (including nanoparticles, oil, electrolyte, and surfactant) summarized and discussed here, includes the most recent accomplishments in gas-liquid mass transfer engineering. This review is expected to inspire new research for future developments and potential applications in scientific research and industry regarding gas-liquid mass transfer engineering. Finally, it presents conclusions and perspectives on enhancing gas-liquid mass transfer.